2017
DOI: 10.2527/tas2017.0043
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of increasing standardized ileal digestible lysine for primiparous and multiparous sows during lactation1,2

Abstract: Two experiments were conducted to evaluate the effects of increasing dietary SID Lys in lactation on sow and litter performance. In Exp. 1, a total of 111 primiparous sows (Line 241; DNA Genetics, Columbus, NE) were allotted to 1 of 4 dietary treatments on d 110 of gestation. Dietary treatments included increasing dietary standardized ileal digestible (SID) Lys (0.80, 0.95, 1.10, and 1.25%). During lactation, there were no differences in ADFI or sow BW at weaning (d 21), resulting in no differences in BW loss.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(58 reference statements)
0
3
0
1
Order By: Relevance
“…Lysine is considered the first-limiting amino acid in cerealsoybean meal-based diets fed to lactating sows (Danielsen, 1992). Previous estimates of dietary standardized ileal digestible (SID) Lys requirements for lactating sows vary considerably from 27 to 70 g/d or 4.9 to 10.5 g/kg diet (NRC, 2012;Xue et al, 2012;Gourley et al, 2017). However, most of the research investigating the dietary Lys requirement was conducted with sows weaning <10 piglets per litter and with litter growth rates of 1.4 to 2.3 kg/d (NRC, 2012), whereas Gourley et al (2017) reported that sows required 70 g/d of SID Lys for a litter growth rate of 2.9 kg/d.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysine is considered the first-limiting amino acid in cerealsoybean meal-based diets fed to lactating sows (Danielsen, 1992). Previous estimates of dietary standardized ileal digestible (SID) Lys requirements for lactating sows vary considerably from 27 to 70 g/d or 4.9 to 10.5 g/kg diet (NRC, 2012;Xue et al, 2012;Gourley et al, 2017). However, most of the research investigating the dietary Lys requirement was conducted with sows weaning <10 piglets per litter and with litter growth rates of 1.4 to 2.3 kg/d (NRC, 2012), whereas Gourley et al (2017) reported that sows required 70 g/d of SID Lys for a litter growth rate of 2.9 kg/d.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have estimated the dietary Lys requirement of lactating sows when supplied via intact protein sources (King et al, 1993;Yang et al, 2000;Gourley et al, 2017). However, very few studies have used the approach of increasing dietary Lys while keeping all other amino acids and nutrients constant (Chen et al, 1978;Knabe et al, 1996;Xue et al, 2012) and none of these had litter growth rates above 2.5 kg/d.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be attributed to the effect of tolerance to endogenous heat sensation by the sow, which this alkaloid provides from the desensitization of TRPV receptors responsible for the sensation of pain and heat in the body [27]. A higher feed intake during lactation or attenuation of catabolism during this phase improves reproductive performance in the subsequent cycle [28].…”
Section: Discussionmentioning
confidence: 99%
“…O número de leitões determina a quantidade de lisina e aminoácidos necessários, e em casos de deficiências nutricionais, as fêmeas mobilizam gordura corporal e proteína para apoiar o crescimento da leitegada (THEIL, 2015). A oferta de aminoácidos dietéticos e proteínas próximo das exigências pode beneficiar a produção de proteína no leite e diminuir a mobilização de proteína muscular em porcas lactantes (GOURLEY et al, 2017;.…”
Section: Lactaçãounclassified